Reviving the design concepts and material culture of paraphernalia and receptacles used for the traditional toddy tapping in Kalutara, Sri Lanka - Sagara Jayasinghe
The artificial extraction of sweet sap, or toddy, from the incised young inflorescences of the coconut palm (Cocos nucifera) has long been a captivating cottage industry in the coastal region of Kalutara, Sri Lanka. Freshly tapped toddy contains little to no alcohol and is considered a nutritious beverage, though it rapidly ferments into an alcoholic drink. Historical references to toddy and its distillation into arrack date back to the fifth century, yet it is widely believed that the current techniques of toddy tapping were introduced to the Kalutara region by the toddy tappers from the tropical coasts of South India during British colonial rule. Drawing on the author's hands-on experience and interviews with the local community who have been involved in toddy-tapping for generations, this paper reviews the design principles and material culture used in the paraphernalia and receptacles used for Kalutara's traditional toddy-tapping industry. These paraphernalia and receptacles, which have been used for decades, demonstrate the community's capacity to craft their implements from sustainable, locally sourced materials. As this study reveals, these traditional techniques and tools continue to provide practical solutions while preserving the rich history and cultural identity of the toddy-tapping communities in the coastal region of Kalutara. The preservation of this traditional knowledge is essential for safeguarding both the cultural heritage and the economic future of the toddy-tapping industry in Sri Lanka.